Development of Economic and Mathematical Models of Optimisation of Expenditures at ore Mining and Processing Enterprises - Ishchenko Mykola I. (Bìznes Inform, 2014)
The goal of the article is development of methodical approaches to identification of the optimal structure of material and labour resources, which ensure the minimum cost value at ore mining and processing enterprises The article conducts analysis of modern studies on issues of management of enterprise expenditures. It shows that one of the most popular methods of expenditure forecasting is economic and mathematical modelling. It proves that when developing economic and mathematical dependencies for forecasting cost value of products it is expedient to develop individual models for each individual enterprise, since this approach helps to take into account unique natural and technological conditions of functioning of ore mining and processing enterprises. The article develops a model of dependence of cost value of products on the level of use of main types of resources at one ore mining and processing enterprise in Kryvyi Rih. On the basis of the developed model the article identifies optimal volumes of use of material and labour resources for a forecasted period. The article shows that the cost value of products, with optimal values of main types of resources, is lower than the forecasted value, obtained through the trend equation. The offered approaches could be used when preparing budgets of expenditures of enterprises for future periods.